2019
DOI: 10.1039/c8sc05178j
|View full text |Cite
|
Sign up to set email alerts
|

A compatible anode/succinonitrile-based electrolyte interface in all-solid-state Na–CO2 batteries

Abstract: A compatible anode/succinonitrile-based electrolyte interface is achieved owing to the in situ formed NaF-rich interphase through an extremely simple approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 59 publications
2
63
0
Order By: Relevance
“…The pattern in Figure 1b shows two characteristic peaks of PEO located at 19.5° and 23.5°, [ 22 ] while the characteristic peaks of SN are located at 20.5° and 28.5° in Figure 1c. [ 23 ] There are no sharp peaks in Figure 1d, indicating an amorphous feature of the PEO‐SN‐NaClO 4 membrane. The disappearance of crystallinity radically boosts the sodium‐ion conductivity of the PEO‐SN‐NaClO 4 membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The pattern in Figure 1b shows two characteristic peaks of PEO located at 19.5° and 23.5°, [ 22 ] while the characteristic peaks of SN are located at 20.5° and 28.5° in Figure 1c. [ 23 ] There are no sharp peaks in Figure 1d, indicating an amorphous feature of the PEO‐SN‐NaClO 4 membrane. The disappearance of crystallinity radically boosts the sodium‐ion conductivity of the PEO‐SN‐NaClO 4 membrane.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] However,s imilar to lithium metal electrodes,Nametal electrodes also suffer from the problems of low Coulombic efficiency, poor cycling stability,and serious safety hazards,w hich results from uncontrolled dendrite formation during Na plating. [4][5][6] To solve such problems of Na metal electrodes,e fforts have been proposed such as manipulating nanostructured scaffolds, [7][8][9][10][11][12] optimizing electrolyte, [13][14][15][16] and engineering artificial protection layers. [17][18][19] Unfortunately,t hese progresses are still difficult to meet the demands of practical applications of Na metal electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Na 2 (CB 11 H 12 )(CB 9 H 10 ) exhibits one of the highest ionic conductivity recorded with 70 mS cm -1 at RT, [4b] while Duchêne et al have reported an operational all-solid-state 3V stable battery based on the Na 4 (B 12 H 12 )(B 10 H 10 ) SE which possesses an ionic conductivity of about 1 mS cm -1 at 20 °C and compatibility with a metallic sodium anode, [5c, 6] where most of other SEs are unstable toward metallic Na. [7] The peculiar anion dynamic within Na 4 (B 12 H 12 )(B 10 H 10 ) was identified as being responsible of the high cation diffusion. [8] In addition, Moury et al studied the behavior of Na 2 B 12 H 12 under pressure and demonstrated its high compressibility with a bulk modulus as low as 14 GPa.…”
Section: Introductionmentioning
confidence: 99%